PEMINDAHAN PEDAGANG PASAR JONGKOK KE KOMPLEK MTC GIANT PANAM (STUDI KASUS PADA PEDAGANG PAKAIAN) - Darni "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Pekanbaru administration Assessing Market Presence Squatting disturbing Panam city. In response to the problems that occur in the market hawkers squat Panam, no form of acceptance and refusal by traders to removal by the city government pekanbaru place. Traders who are willing to move to a place that has been provided by the local government believes "the public will obey the rules that are made, because it is in the common interest". In this issue there are many traders who do not receive transfer performed by the Government of Pekanbaru with various reasons as traders assess the space provided will make it decreases the level of their sales, because the place was originally located on the outskirts of Jalan HR Soebrantas has been known by many people who selling there.In this study, the research subjects were 10 clothing merchant who had been relocated by the city government complex in Pekanbaru Panam MTC Giant selection of research subjects using Snow Ball Sampling techniques. From the research, Conflict and resistance are always colored the relationship between street vendors with city government pekanbaru but has now led to a peaceful and pre traders who sell in the market squat in Jlan HR Soebrantas willing to be relocated in complex MTC Giant. Street vendors set only in terms of order and beauty of the city, the impact of the relocation of the traders is less a concern to governments' market vendors in the complex relocated squat Giant MTC. From the results of the study also found that the impact is felt by various merchants, including a decrease in the level of income, level of turnover and increasing costs lmenjadi oprasioan thereby increasing economic hardship to the lives of street vendors.Keywords: Street vendors, Relocation, Perception